High-resolution 3D strain and orientation mapping within a grain of a directed energy deposition laser additively manufactured superalloy - Chen, Y; Tang, YT; Collins, DM; Clark, SJ; Ludwig, W; Rodriguez-Lamas, R; Detlefs, C; Reed, RC; Lee, PD; Withers, PJ; Yildirim, C (Elsevier, 2023)
The industrialization of Laser Additive Manufacturing (LAM) is challenged by the undesirable microstructures and high residual stresses originating from the fast and complex solidification process. Non-destructive assessment of the mechanical performance controlling deformation patterning is therefore critical. Here, we use Dark Field X-ray Microscopy (DFXM) to map the 3D subsurface intragranular orientation and strain variations throughout a surface-breaking grain within a directed energy deposition nickel superalloy. DFXM results reveal a highly heterogenous 3D microstructure in terms of the local orientation and lattice strain. The grain comprises ≈ 5 µm-sized cells with alternating strain states, as high as 5 ×10−3 , and orientation differences <0.5°. The DFXM results are compared to Electron Backscatter Diffraction measurements of the same grain from its cut-off surface. We discuss the microstructure developments during LAM, rationalising the development of the deformation patterning from the extreme thermal gradients during processing and the susceptibility for solute segregation.